Adverse Effects of Computer Work on Human Health - Abdujabborov Madaminjon Vohidjon ogli; Ahmadaliyev Boburjon Botirjon ogli (Zien Journals, 2022)
This article gives you a brief overview on computers and how to prevent them. It is recommended that you read this before using the computer.
Keywords: Computer; information; electromagnetic; technology